CFD and comparative study on the dual-function solar collectors with and without tile-shaped covers in water heating mode. (February 2016) - He, Wei; Hong, Xiaoqiang; Luo, Bingqing; Chen, Hongbing; Ji, Jie
Abstract: This paper presents a dedicated study of a novel tile-shaped dual-function solar collector in water heating mode by using computational fluid dynamics (CFD). This system employs a modular panel incorporating tile-shaped covers that is able to serve as part of building pitched roof, thus creating a building integrated, highly efficient and aesthetically appealing solar heating structure, particularly suitable for the Chinese traditional buildings. A complete 3D CFD model was developed. The numerical prediction was validated using experimental data. It was found that the established model is able to predict the operational performance of the system at reasonable accuracy. With the specified system structure, the efficiency of the solar system was found to be a function of its operational conditions. The results indicated that lower inlet water temperature, higher water flow rate, higher ambient air temperature and lower solar radiation led to enhanced thermal efficiency of the module. Further, the performance of the dual-function solar collector with and without tile-shaped covers was comparatively studied. It was found that the tile-shaped collector is able to achieve higher efficiency at higher temperature operation. This work outlines the impacts of the main operational conditions to the tile-shaped dual-function solar collector's efficiency. Highlights: A new tile-shaped dual-function solar collector was described. CFD investigation of the collector in water heating model was presented. The impact of the operating conditions was investigated. The tile-shaped covered collector has lower heat loss coefficient than flat one.